Recycling and reusing of waste fresh cement mortar through the dormancy-awakening method - Wang, Liang; Wang, Chenglong; Li, Qi; Xu, Jian; Wang, Xiaodong; Zhou, Jian; Wang, Hao (Archives of Civil Engineering, 2026)
This study develops the dormancy-awakening method for recycling and reusing of waste fresh cement mortar. Sucrose (SU, C12H22O11) is utilized as the dormancy agent to delay cement hydration, which can prolong the storage time of the waste fresh cement mortar. Aluminum sulfate (AS, Al2(SO4)3) and calcium formate (CF, C2H2O4Ca) serve as awakening agents to resume cement hydration. The results show that the addition of 0.1% SU in fresh mortar blocks cement hydration for the first 24 hours. AS and CF accelerate the cement hydration process and shorten the setting time. The combined use of AS and CF can further accelerate cement hydration, leading to the normal setting time of cement. The setting time can be flexibly controlled by using dormancy agent and awakening agents. Moreover, the awakened cement mortar has smaller volume of harmful pores compared to normal mortar. The addition of awakening agents can improve elastic modulus and packing density of the hardened mortar according to nanoindentation analysis. Compared to the normal mortar, the compressive strength of awakened mortar is enhanced by 21.0% and 18.3% at 3 days and 28 days, respectively. This study develops the method for recycling and reusing waste fresh cement mortar by using conventional admixtures.